2004
DOI: 10.2193/0022-541x(2004)068[0223:asemdf]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Spatially Explicit Model, Derived From Demographic Variables, to Predict Attitudes Toward Black Bear Restoration

Abstract: Understanding human attitudes often is vital to the success of restoration projects, especially those involving controversial species such as carnivores. Support for restoration activities may differ depending on residence location of the respondent; thus, understanding the spatial distribution of attitudes is important when selecting suitable restoration sites. We used black bear (Ursus americanus) restoration as an example of how to calculate and use a spatially explicit model of human attitudes based on dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Among the stronger relationships, several studies have reported older (versus younger) individuals to have relatively negative attitudes toward wildlife (e.g., Bowman et al 2004;Morzillo et al 2007;Decker et al 2001), whereas attitude differences between sexes vary by situation. In addition, although more positive attitudes toward wildlife are typically more likely among individuals with more formal education (e.g., Bowman et al 2004;Decker et al 2001), this relationship was significant only for SAMO. As a result of factor analysis, we suspect that the weak (but significant) relationship between household size and attitudes toward rodents in SAMO is related to concern about household welfare as a result of rodent presence.…”
Section: Discussionmentioning
confidence: 99%
“…Among the stronger relationships, several studies have reported older (versus younger) individuals to have relatively negative attitudes toward wildlife (e.g., Bowman et al 2004;Morzillo et al 2007;Decker et al 2001), whereas attitude differences between sexes vary by situation. In addition, although more positive attitudes toward wildlife are typically more likely among individuals with more formal education (e.g., Bowman et al 2004;Decker et al 2001), this relationship was significant only for SAMO. As a result of factor analysis, we suspect that the weak (but significant) relationship between household size and attitudes toward rodents in SAMO is related to concern about household welfare as a result of rodent presence.…”
Section: Discussionmentioning
confidence: 99%
“…Topics covered have included general attitudes toward bears (Decker, Brown, Hustin, Clarke, & O'Pezio, 1981;Kellert, 1994), attitudes toward bear hunting and hunting methods (Loker & Decker, 1995;Teel, Krannich, & Schmidt, 2002), tolerance of human-bear conflict (Organ & Ellingwood, 2000;Seimer & Decker, 2003), and support for local recovery of extirpated or threatened bear populations (Bowman, Leopold, Vilella, & Gill, 2004;Morzillo, Mertig, Garner, & Liu, 2007;Rice, Ballard, Fish, Wester, & Holdermann, 2007). Recent studies have also examined the acceptability of specific management actions for addressing human-bear conflicts in urban areas Whittaker et al, 2006 Many of these studies have incorporated measures of attitudes toward bears and/ or their management.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…First, bear managers will likely be met with different opinions when outreach takes place in any location, which makes generalizing results to a larger area (e.g., census block groups; Bowman et al, 2004) and customizing outreach programs for specific locations difficult. Second, movement of urban residents into rural areas may result in amalgamation of urban versus rural wildlife values.…”
Section: Tablementioning
confidence: 99%